2016
DOI: 10.2215/cjn.06300615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tolvaptan in Autosomal Dominant Polycystic Kidney Disease by CKD Stage: Results from the TEMPO 3:4 Trial

Abstract: Background and objectives The Tolvaptan Efficacy and Safety in Management of Autosomal Dominant Polycystic Kidney Disease and Its Outcomes 3:4 study demonstrated a significant beneficial effect of the vasopressin V2 receptor antagonist tolvaptan on rates of kidney growth and eGFR decline in autosomal dominant polycystic kidney disease (ADPKD). This post hoc analysis was performed to reassess the primary and secondary efficacy endpoints by CKD stage at baseline.Design, setting, participants, & measurements In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 24 publications
4
109
0
8
Order By: Relevance
“…that information cannot be determined from the present trial, a post hoc analysis of data from patients with chronic kidney disease of stage 3 in the TEMPO 3:4 trial showed a treatment effect of 1.67 ml per minute per 1.73 m 2 per year, which was incremental over the 3 years of that trial. 26 In the present trial, the baseline estimated GFR was 41.1 ml per minute per 1.73 m 2 and declined over a 1-year period by 4.17 ml per minute per 1.73 m 2 with placebo. If one assumes that tolvaptan treatment would continue to slow the decrement in the estimated GFR by 1.27 ml per minute per 1.73 m 2 per year, the time to chronic kidney disease of stage 5 would be extended from 6.2 years to 9.0 years.…”
mentioning
confidence: 43%
See 2 more Smart Citations
“…that information cannot be determined from the present trial, a post hoc analysis of data from patients with chronic kidney disease of stage 3 in the TEMPO 3:4 trial showed a treatment effect of 1.67 ml per minute per 1.73 m 2 per year, which was incremental over the 3 years of that trial. 26 In the present trial, the baseline estimated GFR was 41.1 ml per minute per 1.73 m 2 and declined over a 1-year period by 4.17 ml per minute per 1.73 m 2 with placebo. If one assumes that tolvaptan treatment would continue to slow the decrement in the estimated GFR by 1.27 ml per minute per 1.73 m 2 per year, the time to chronic kidney disease of stage 5 would be extended from 6.2 years to 9.0 years.…”
mentioning
confidence: 43%
“…19,26 (Data from the Japanese patients in the TEMPO 3:4 trial were not included in the power calculations because the present trial [REPRISE] was not planned to include Japanese patients.) The analyses of all the efficacy end points were performed according to the intention-to-treat principle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They exhibit a hyper-proliferative and pro-apoptotic phenotype 5 , eventually leading to end-stage renal disease. Tolvaptan, a v2-specific vasopressin receptor antagonist, is the first drug approved for the treatment of ADPKD, however additional therapeutic targets are needed because tolvaptan is not curative and side effects preclude treatment in some patients 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Goals and limits for safe correction are similar to those described above in the treatment of chronic hyponatraemia. Hepatotoxicity with tolvaptan is a concern based on the TEMPO trial (this trial examined the effect of tolvaptan, at high dose, on the progression of polycystic kidney disease); 57 it is therefore recommended to check liver enzymes in patients taking tolvaptan. Another potential limitation to the use of vaptan therapy is that its cost may be prohibitive.…”
Section: Vaptansmentioning
confidence: 99%